Toward understanding individuals acceptance of internet of things based services: Developing an instrument to measure the acceptance of smart meters - Alkawsi G.A.; Ali N.B.; Alghushami A. (Little Lion Scientific, 2023)
The benefits of new technology can only be realized when and if the new technology is widely accepted and used. Understanding the factors that may determine of an individuals willingness to use new technology is important to improve the success rate of the implementation. The use of a smart meter as an internet-of-things based device is the focus of this study. The smart meter is a power energy saving device that aims to enable consumers to have more control of their energy usage and save money. Apparently, there is still a lack of acceptance of smart meter services among consumers. This study proposed a conceptual model using the unified theory of acceptance and use of technology (UTAUT2) as its underlying theories. A survey instrument was developed by using existing scales from prior instruments and by creating additional items, which might appear to fit the construct definition. The pilot study was conducted by distributing the survey to 32 users of a smart meter in order to evaluate the reliability and validity of the instruments prior to performance of a full scale survey. The results showed that the reliabilities of all scales in the survey instrument were above the target acceptance level. 2005 ongoing JATIT & LLS.